Development of Articulate Storyline 3 Interactive Multimedia for IPAS Learning in Elementary Schools - sil_via28 (Journal of Education and Teaching Learning, 2026)
This study addresses the critical challenge of monotonous and text-centered instructional delivery in primary schools by developing an interactive multimedia application utilizing Articulate Storyline 3 incorporated with the structural syntax of the Discovery Learning model. Focused on the sub-topic of regional cultural heritage within the fifth-grade Science and Social Studies (IPAS) curriculum, this study adopts a Research and Development (R&D) methodology guided by the ADDIE design framework (Analysis, Design, Development, Implementation, Evaluation). Data collection employed expert appraisal instruments, comprehensive user perception surveys, and cognitive pretest-posttest protocols. Quantitative assessment revealed exceptional validity, with mean ratings of 86.67% from instructional content specialists, 91.25% from linguistic experts, and 92.50% from media engineers. User experience evaluations indicated outstanding operational practicality, scoring 90.67% from educators and 91.56% from learners. Empirical analysis demonstrated a substantial leap in academic achievement, with the collective mean score ascending from 61.67 during the pretest to 86.11 in the posttest phase, facilitating a classical mastery attainment of 94.44%. The investigation proves that the application successfully minimizes abstract conceptual boundaries, significantly enhances cognitive absorption, and presents an innovative technological framework for child-centered digital pedagogy.